A Systematic Review Of Literature On The Association Among Sleep, Cortisol Level And Cardiovascular Health Within The Healthcare Shift Worker Population - Aslah Nabilah Abdull Sukor; Norsham Juliana Nordin; Nazefah Abdul Hamid; Nur Islami Mohd Fahmi Teng; Muslimah Ithnin (MDPI, 2026)
Indexed by WOS / SCOPUS / ERA